Acute dairy milk ingestion does not improve nitric oxide-dependent vasodilation in the cutaneous microcirculation - Alba, Billie K.; Stanhewicz, Anna E.; Kenney, W. Larry; Alexander, Lacy M. (British journal of nutrition, 2016)
In epidemiological studies, chronic dairy milk consumption is associated with improved vascular health and reduced age-related increases in blood pressure. Although milk protein supplementation augments conduit artery flow-mediated dilation, whether or not acute dairy milk intake may improve microvascular function remains unclear. We hypothesised that dairy milk would increase direct measurement of endothelial nitric oxide (NO)-dependent cutaneous vasodilation in response to local skin heating. Eleven men and women (61 (sem 2) years) ingested two or four servings (473 and 946 ml) of 1 % dairy milk or a rice beverage on each of 4 separate study days. In a subset of five subjects, an additional protocol was completed after 473 ml of water ingestion. Once a stable blood flow occurred, 15 mm-N G -nitro-l-arginine methyl ester was perfused (intradermal microdialysis) to quantify NO-dependent vasodilation. Red-blood-cell flux (RBF) was measured by laser-Doppler flowmetry, and cutaneous vascular conductance (CVC=RBF/mean arterial pressure) was calculated and normalised to maximum (%CVCmax; 28 mm-sodium nitroprusside). Full expression of cutaneous vasodilation was not different among dairy milk, rice beverage and water, and there was no effect of serving size on the total vasodilatory response. Contrary to our hypothesis, NO-dependent vasodilation was lower for dairy milk than rice beverage (D: 49 (sem 5), R: 55 (sem 5) %CVCmax; P<0·01). Acute dairy milk ingestion does not augment NO-dependent vasodilation in the cutaneous microcirculation compared with a rice beverage control.